Factors affecting destination innovation and competitiveness at destinations in the central highlands, Vietnam - Long, Nguyen Thanh; Khanh, Pham Ngoc Kim; Trung, Nguyen Quoc; Linh, Nguyen My; Phat, Tong Thanh; Nhung, Le Hong; Vy, Phan Thi Ha; Khoa, Tran Dang (Journal of Tourism Management Research, 2023)
This study aims to determine the factors affecting both destination innovation and the competitiveness of the tourism destinations in the Central Highlands, Vietnam. This research used both qualitative and quantitative research methods. The qualitative research method was used through focus group interviews and one-on-one interviews in order to complete the research model and scales. In addition, SmartPLS software was used to analyse the reliability, convergent validity, and discriminant validity of the quantitative research method. The proposed hypotheses and research model were also examined via boostrapping with P-values ≤ 0.05. This study had a 210-expert survey of managers and experienced executives working in the tourism industry in the Central Highlands, Vietnam. The research findings showed four factors affecting competitiveness through innovation, which was a moderating factor among destinations in the Central Highlands of Vietnam, including Policies, Local specialties, Culture, and Natural environment. From these findings, some policy implications were proposed for destinations and tourism managers to develop and enhance destination innovation and competitiveness at destinations in the Central Highlands, Vietnam, through the improvement of Policies, Local specialties, Culture, and Natural environment. In addition, these implications also aim to realize sustainable tourism development for the region, which is one of the most potential tourism regions in Vietnam.